2018
DOI: 10.4025/actascianimsci.v41i1.36493
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sorghum silage with leucaena

Abstract: This study evaluated the effect of increasing levels of leucaena forage in sorghum: forage. In addition to pure sorghum, it was evaluated different levels of inclusion of leucaena (15, 30 and 50%) at the time of ensiling. Forage was ensiled in PVC tubes (100 mm diameter, 500 mm length) under the density of 500 – 600 kg m-3, a total of 20 silos were prepared, which were opened 35 days after ensiling. There was no effect (p > 0.05) of leucaena inclusion levels for pH, water activity (Aw) and total ammonia nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…In all sorghum cultivars, ideal NDF levels were observed, which is closely correlated with dry matter intake, since values above 60% are negatively correlated with forage intake (Mertens, 1987;Van Soest, 1965). Andrade et al (2019) obtained similar values to those found in this study.…”
Section: First Seasonsupporting
confidence: 88%
“…In all sorghum cultivars, ideal NDF levels were observed, which is closely correlated with dry matter intake, since values above 60% are negatively correlated with forage intake (Mertens, 1987;Van Soest, 1965). Andrade et al (2019) obtained similar values to those found in this study.…”
Section: First Seasonsupporting
confidence: 88%
“…Legumes naturally present a higher CP compared to other forage resources [40,41]. Therefore, their addition to silages can increase their nutritional value [42][43][44]. Silage from PPPG intercropping can be an important alternative when other protein sources are lacking and/or are too expensive to compose the ruminant diet.…”
Section: Fm and Chemical Composition Of The Silagementioning
confidence: 99%
“…For example, silages with greater inclusion of Leucaena (60 and 80% inclusion) presented pH values above the limit (3.8-4.2) recommended by McDonald et al (1991). This effect is attributed to the high buffering capacity of Leucaena (Gandra et al, 2017) associated with its low content of soluble carbohydrates (Andrade et al, 2018).…”
Section: Discussionmentioning
confidence: 99%